An Introduction to Exdysivity Index for Organizational Change Capability Assessment - Thammatucharee, Yanyong (Open Science Journal, 2017)
The dynamic change capabilities of organizations are prerequisite to the success, long-term growth and sustainability (Moran & Brightman, 2000; Andreeva & Victoria, 2006; Barreto, 2010; Halkos, 2012). Although organization development (OD) study involves planned changes that would help businesses to stay competitive in the marketplace, there is no effective and reliable change indicator that can reflect the need and level of change capabilities. Apparently, organizational change management requires multi-perspectives approach rather than a single approach to all change situations (Andreeva, 2008). To achieve the successful and sustainable change, an effective change measurement is the key (Moran, Baird & Brightman, 2000). This study aims to propose the development idea for a change indicator or so-called “exdysivity index (EI)” as the change capability assessment and requirement for change intervention at both international and individual organization level.